Modeling of magnetostrictive strain in soft magnetic elastomers - Raikher, Yuriy L'vovich; Stolbov, Oleg Valerievich (Computational Continuum Mechanics, 2009)
The origin of magnetic striction of a soft magnetic elastomer, i.e., its elongation/contraction under an applied uniform magnetic field in the absence of mechanical load is considered. Qualitative analysis shows that the external field has a two-fold effect on the medium. One of the mechanisms manifests itself at the macroscopic level, while the other-at the mesoscopic one. The latter, structural, magnetostriction mechanism depends crucially on the details of the short-range order of the magnetic particle spatial distribution in the elastomer matrix. To prove this conclusion, numerical modeling of the behavior of two-dimensional assemblies of magnetic particles embedded in an elastic layer is carried out. It is shown that it is indeed the presence/absence of multi-particle clusters which causes the difference in both the sign and the magnitude of magnetostriction in otherwise identical materials.
Keywords: soft magnetic elastomers; magnetorheological elastomers; magnetostriction; modeling of strains